Case 3709: Conservation of the usage of names of western North American Hesperia comma-group subspecies (Lepidoptera, Hesperiidae) through designation of neotypes for Pamphila colorado Scudder, 1874, Pamphila manitoba Scudder, 1874, Pamphila cabelus Edwards, 1881, Pamphila harpalus Edwards, 1881, Pamphila idaho Edwards, 1883, Pamphila oregonia Edwards, 1883, and Hesperia colorado ochracea Lindsey, 1941 - Scott, James A; Kondla, Norbert G; Emmel, John F; Davenport, Kenneth E; Mattoon, Sterling O; Fisher, Michael S; Guppy, Crispin S; Kohler, Steve; Patterson, William D; Opler, Paul A; Westwood, A Richard; Royer, Ronald A (Bulletin of Zoological Nomenclature, 2018)
The purpose of this case, under Articles 15.2.1, 45.6.4.1, 75.5, 75.6, 76, and 81 of the Code, is to eliminate nomenclatural chaos within Hesperia comma-group butterflies in western North America caused by seven lectotypes and a holotype whose appearance and inadequate or mislabeled localities do not allow their taxonomic identity to be determined, by employing Art. 75.5 to designate seven neotypes for the following names: Pamphila colorado Scudder 1874, Pamphila manitoba Scudder, 1874, Pamphila cabelus Edwards, 1881, Pamphila harpalus Edwards, 1881, Pamphila idaho Edwards, 1883, Pamphila oregonia Edwards, 1883, and Hesperia colorado ochracea Lindsey, 1941. The neotypes will provide stable names for nine taxa and conserve six names that have been in prevailing usage for many decades.
Keywords: Nomenclature; taxonomy; Insecta; Lepidoptera; HESPERIIDAE; Hesperia; Pamphila; Pamphila assiniboia; Pamphila cabelus; Pamphila colorado; Papilio comma; Pamphila harpalus; Pamphila idaho; Pamphila manitoba; Hesperia ochracea; Pamphila oregonia; Hesperia oroplata; Hesperia sublima; Hesperia yosemite; western North America; Sierra Nevada; California; Colorado; Nevada; Alberta; British Columbia; Manitoba